Surgical training in the Caribbean: The past, the present, and the future - Newnham, Mark S.; Dan, Dilip; Maharaj, Ravi; Plummer, Joseph Martin (Frontiers in Surgery, 2023)
The nine million inhabitants of these diverse English-speaking Caribbean are grateful to the University of the West Indies which been central in the independent training of surgical specialists in all areas of surgery for the past 50 years. Globalization and access to information has revealed that the quality training and surgical care being delivered can be further improved. Technological advances will perhaps never be on par with higher income countries but collaborative ventures with Global Health partners and institutions can ensure that the people of the Region will have appropriately trained surgical doctors and therefore the provision of accessible quality care will remain a staple, with even the possibility of income generation.